2022
DOI: 10.1097/pas.0000000000001992
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Multifocal Granular Cell Tumors

Abstract: Granular cell tumors (GrCT) were recently found to be driven by inactivating mutations in vacuolar H+-ATPase (V-ATPase) genes, most frequently ATP6AP1 and ATP6AP2. Multifocal presentation is present in ~10% of cases; however, the relationship between multifocal tumors in a given patient has not been elucidated. We hypothesized that benign-appearing multifocal GrCT are molecularly distinct whereas paired primary and metastatic malignant GrCT share identical mutations. To test this, we conducted targeted next-ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Further, multifocal GCTs within a given patient were molecularly distinct, supporting interpretation as separate primaries. In contrast, paired primary and metastatic histologically malignant GCTs showed identical mutations, confirming the primary-metastatic relationship [ 17 ]. Wei et al [ 18 ] reported whole exome sequencing (WES) performed in a malignant GCT that exhibited low mutation burden and overall stable genome with local complex rearrangements.…”
Section: Discussionmentioning
confidence: 91%
“…Further, multifocal GCTs within a given patient were molecularly distinct, supporting interpretation as separate primaries. In contrast, paired primary and metastatic histologically malignant GCTs showed identical mutations, confirming the primary-metastatic relationship [ 17 ]. Wei et al [ 18 ] reported whole exome sequencing (WES) performed in a malignant GCT that exhibited low mutation burden and overall stable genome with local complex rearrangements.…”
Section: Discussionmentioning
confidence: 91%
“…In 2018, Pareja et al performed whole exome sequencing of benign and malignant GCTs and identified inactivating mutations of ATP6AP1 and ATP6AP2 in 49-74% [92,[97][98][99]. In vitro inactivation impairs the V-ATPase gene complex in Schwann cells and leads to the formation of GCTs [97].…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…In vitro inactivation impairs the V-ATPase gene complex in Schwann cells and leads to the formation of GCTs [97]. Dehner et al demonstrated in 2022 that multifocal benign GCTs in the same patient are molecularly distinct, whereas multifocal malignant GCTs, which are much less common, harbor identical mutations [99].…”
Section: Granular Cell Tumorsmentioning
confidence: 99%
“…A multifocal benign variant also exists. 3 In addition there are reports of atypical and malignant GCTs with junctional components that raise a differential diagnosis of melanoma. 4 There are also reports of nevi and melanomas with granular cell cytoplasmic change.…”
Section: Introductionmentioning
confidence: 99%
“…Criteria have been proposed for distinguishing benign, atypical, and malignant GCTs 1,2 ; however, these are difficult to apply consistently and there are case reports of GCTs with benign histopathologic features going on to metastasize. A multifocal benign variant also exists 3 . In addition there are reports of atypical and malignant GCTs with junctional components that raise a differential diagnosis of melanoma 4 .…”
Section: Introductionmentioning
confidence: 99%